Icatforlearning Website for Teaching Translation and Interpreting Online Class (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
COVID-19 pandemic spreads worldwide, and educational sectors have received significant impacts because of it. Schools and Universities try to find a new method for the continuation of the teaching and learning process. As a result, online learning during the COVID-19 pandemic is rising. To support this learning, technology and new media are needed. One of the online media used by lecturers in teaching translation and interpreting is the icatforlearning website. It was designed to fulfill the students’ and lecturers’ needs in the teaching and learning process. This research aimed to portray the use of the icatforlearning website in translation and interpreting classes and find the obstacles students face using that website. This study used qualitative research. The subjects are the students of translation and interpreting class in the English Department. There are four classes for translation and interpreting class. The data were collected through observation and interviews. The result shows that icatforlearning can support the online teaching and learning process, although the students faced a few obstacles.